The Applying of Cognitive Strategy Instruction in Writing (CSIW) To Increase the students’ Writing Abilities - Badaruddin; St. Hajar L; Nurhamida Hamma (EDUVELOP, 2022)
This research is based on students' problems related to learning English, especially writing English. this is due to the very poor quality of their writing. therefore, the purpose of this study was to find out whether the use of strategy CSIW in learning English can help improve students' writing skills in class X TITL B SMK Negeri 2 Parepare. The researcher applied a pre-experimental method using a one-group pre-test and post-test design, using the sample X TITL B, which consisted of 36 students from SMK Negeri 2 Parepare by using cluster sampling of 72 students from the population. The results of the data analysis showed that the students' writing ability increased significantly. This is indicated by the average score of students from the pre-test results (48.77) and the average score of students from the post-test is 80.03. This indicated that the writing ability of students in class X TITL B at SMK Negeri 2 Parepare has progressed by the use of the strategy CSIW to improve students' descriptive writing skills. This is proved by the t-test value (3.11) which is higher than the t-table value (1.689).